Film jako kulturowa przestrzeń edukacji nieformalnej - Pilawska, Roksana (Studia Edukacyjne, 2021)
The article attempts to theoretically and methodologically capture the potential and possibilities of films within informal education. The author begins by reflecting on the importance of popular culture in the process of shaping the identity of the individual and then proceeds to determine the contemporary role of informal education and the importance of film as an educational medium (in reference to the previously applicable communication model and cognitive theory). In the further part of the article, in order to determine the current discourse, the author tries to present in an orderly manner both well-known and newer concepts in the field of film (originating from various fields of science). As a summary, the author refers to contemporary trends that seem to be followed by the latest research and practical activities related to film education.